The Impact of Metolachlor Applications and Phytoremediation Processes on Soil Microorganisms: Insights from Functional Metagenomics Analysis - Seyedeh Parvin Hejazirad; Caique Menezes de Abreu; Guilherme Henrique Fernandes Carneiro; Carlos Rodrigues Gomes; Paulo Roberto de Carvalho Spinola Filho; Márcia Regina da Costa; José Barbosa dos Santos (MDPI AG, 2024)
This study assessed the impact of phytoremediation on reducing the residual concentration of metolachlor in soil treated with doses of 530.7 and 1061.4 g/ha and its effect on microbial biodiversity in contaminated areas. For the plant species Avena sativa and Medicago sativa, a significant efficacy of 54.5 and 36.4% was observed in the dissipation of the herbicide, especially at higher doses. Although metolachlor application reduced soil microbial biodiversity, phytoremediating plants, especially M. sativa, promoted greater richness and distribution of microbial species, mitigating the negative effects of the herbicide. Principal component analysis revealed the influence of these plants and metolachlor on the composition of the microbial community. These results highlight the importance of phytoremediation in promoting soil biodiversity and reducing herbicide contamination, providing crucial insights for remediation strategies in contaminated areas.